Applications of omics and nanotechnology to improve pig embryo production in vitro. Issue 11 (3rd September 2019) - Lucas, Caroline G.; Chen, Paula R.; Seixas, Fabiana K.; Prather, Randall S.; Collares, Tiago
Abstract: An appropriate environment to optimize porcine preimplantation embryo production in vitro is required as genetically modified pigs have become indispensable for biomedical research and agriculture. To provide suitable culture conditions, omics technologies have been applied to elucidate which metabolic substrates and pathways are involved during early developmental processes. Metabolomic profiling and transcriptional analysis comparing in vivo ‐ and in vitro‐derived embryos have demonstrated the important role of amino acids during preimplantation development. Transcriptional profiling studies have been helpful in assessing epigenetic reprogramming agents to allow for the correction of gene expression during the cloning process. Along with this, nanotechnology, which is a highly promising field, has allowed for the use of engineered nanoplatforms in reproductive biology. A growing number of studies have explored the use of nanoengineered materials for sorting, labeling, and targeting purposes; which demonstrates their potential to become one of the solutions for precise delivery of molecules into gametes and embryos. Considering the contributions of omics and the recent progress in nanoscience, in this review, we focused on their emerging applications for current in vitro pig embryo production systems to optimize the generation of genetically modified animals. Abstract : Based on the fact that genetically modified pigs are becoming increasingly utilized for agricultural and biomedical purposes, there is a great potential to integrate nanotechnology approaches in the in vitro pig embryo production system.